The Influence Of Transformational Leadership Style And Job Training On Teacher Performance - Indra Gunawan Gunawan; Sri Sudiarti (JIEMAN: Journal of Islamic Educational Management, 2026)
Improving teacher performance has become a strategic priority for enhancing educational quality, particularly amid the increasing demands placed on schools in the digital era. Although transformational leadership and work ethic have been widely recognized as important determinants of organizational performance, empirical evidence examining their combined influence on teacher performance in secondary education remains limited. This study aims to investigate the effects of transformational leadership and work ethic on teacher performance at SMPN 3 Sukahening. A quantitative research design was employed using a saturated sampling technique, involving all 45 teachers as research participants. Data were collected using a structured questionnaire on a five-point Likert scale and analyzed using multiple linear regression in SPSS version 26. The findings indicate that transformational leadership has a significant positive effect on teacher performance by fostering motivation, creativity, and intellectual stimulation. Likewise, a strong work ethic contributes significantly to improved instructional effectiveness, professional responsibility, and work efficiency. Simultaneously, both variables exert a significant positive influence on teacher performance, highlighting their complementary role in strengthening educational effectiveness. These findings contribute to the human resource management literature by providing empirical evidence of the importance of integrating visionary leadership with a strong professional work ethic to improve teacher performance. Practically, the study offers strategic insights for school leaders to develop transformational leadership practices and cultivate a positive work culture that supports sustainable improvements in educational quality.